Spectrofluorimetric determination of adrenaline and dopamine . - Mohamed Dhamra; Theiaa Al-Sabha; mohammed Al-Enizzi (College of Education for Pure Sciences, 2022)
A sensitive fluorometric method, with few steps and suitable for the daily routine, was made for examining adrenaline hydrochloride and dopamine hydrochloride. The reliance in this paper was on the nucleophilic substitution interaction of the mentioned drugs with 1,2-naphthoquinone sulfonate (NQS) in an aqueous pH 6 to give a fluorescent product with a maximum emission wave at ʎem 471 nm after being excited at a maximum excitation wave at ʎ ex 300 nm. The plots have complied within the range of 0.01- 4.0, 0.01-2 µg/ml, and The detection limits (0.0062, 0.0027) and quantitation limits were (0.0207, 0.0091) µg/ml, for adrenaline and dopamine respectively. The accuracy (% recovery) was between (99.21% - 100.72%) and the relative standard deviation (RSD%) is better than 0.95%. It was also found that the formed product was in a ratio of 1:2 reagent to the drug. The estimation of adrenaline and dopamine has been successfully tested on the injection, and it is in good agreement with its approved value and with that of the British Pharmacopoeia method.